International Aspects of Segment Disclosures: A Conceptual Approach. - Massoud, Marcos F.; Moriarty, Shane R. (The Accounting Review, 1990)
Abstract Reviews the book `International Aspects of Segment Disclosures: A Conceptual Approach,' by Lee H. Radebaugh.